2017
DOI: 10.18203/2320-6012.ijrms20175703
|View full text |Cite
|
Sign up to set email alerts
|

Utility of vest high frequency chest wall oscillation device versus flutter device in acute exacerbation of chronic obstructive pulmonary disease

Abstract: Background: Objectives to assess the effectiveness of high frequency chest wall oscillation (HFCWO) vest system and Flutter devices in the treatment of patients with AECOPD, and to compare the efficacy of HFCWO vest system versus Flutter devices.Methods: We conducted an interventional study on 108 out of 129 patients presented with AECOPD, recruited from two-university hospitals. They were classified into three groups, HFCWO group (n=37), Flutter group (n=35), and control group (n=36). The HFCWO group and Flut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…3,4 Several studies have demonstrated the clinical efficacy of HFCWO treatment at improving treatment compliance, reducing symptoms of dyspnea, increasing oxygen saturation, improving lung function, increasing secretion discharge, and reducing pneumonia, with no particular side-effects. [5][6][7][8][9][10] Most commercial HFCWO devices, such as the VEST, Monarch, MetaNeb (Hill-Rom Services Inc., Wilmington, DE, USA), MedPulse, SmartVest, (Electromed Inc., MN, USA), CareWay (Korust Co. Ltd., Anyang, Korea), inCourage (RespirTech, Plymouth, MN, USA), BiWaze (ABM Respiratory Care, LLC, Eagan, MN, USA), and RespIn 11 (Resp Innovation, Seillans, France), contain an air-pulse generator in the main body that generates necessary pneumatic power for chest wall vibration treatment. This independent-actuating mechanism is most favorable for out-of-hospital treatment (e.g., home or office).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Several studies have demonstrated the clinical efficacy of HFCWO treatment at improving treatment compliance, reducing symptoms of dyspnea, increasing oxygen saturation, improving lung function, increasing secretion discharge, and reducing pneumonia, with no particular side-effects. [5][6][7][8][9][10] Most commercial HFCWO devices, such as the VEST, Monarch, MetaNeb (Hill-Rom Services Inc., Wilmington, DE, USA), MedPulse, SmartVest, (Electromed Inc., MN, USA), CareWay (Korust Co. Ltd., Anyang, Korea), inCourage (RespirTech, Plymouth, MN, USA), BiWaze (ABM Respiratory Care, LLC, Eagan, MN, USA), and RespIn 11 (Resp Innovation, Seillans, France), contain an air-pulse generator in the main body that generates necessary pneumatic power for chest wall vibration treatment. This independent-actuating mechanism is most favorable for out-of-hospital treatment (e.g., home or office).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Several studies have demonstrated the clinical efficacy of HFCWO treatment at improving treatment compliance, reducing symptoms of dyspnea, increasing oxygen saturation, improving lung function, increasing secretion discharge, and reducing pneumonia, with no particular side-effects. 510…”
Section: Introductionmentioning
confidence: 99%